A phylogenetic analysis of lizards of the Liolaemus chiliensis group (lguania Tropiduridae) - Lobo Gaviola, Fernando Jose (2001)
The lizard genus Liolaemus includes over 160 species of which almost h lf are in the chiliensis group. Although some researchers have attempted to define smaller species groups within this large clade, the relationships among the taxa within the group as a whole remain enigmatic. The objectives of this study were to (1) identify characters that will be useful for present and future phylogenetic studies of this group, and (2) generate preliminary phylogenetic hypotheses for taxa within this large clade of lizards. I examined more than 800 specimens of 73 taxa belonging to the chiliensis group from which I identified 55 phylogenetically informative morphological characters. Additional characters (6) were derived from published and unpublished data on chromosomes, life history, and ecology. Four species considered basal for the genus were taken as outgoups. A tree-building program (PAUP 4.0b2) recovered three trees of length 1 1 . 516 (Retention index: 0.59). Differences found among these topologies were restricted to the relationships of species of the elongatus group, in which monophyly was recovered in only one tree . . Results from PAUP's analysis support the monophyly of several previously proposed species groups: alticolor, altissimus, gravenhorstii, hellmichi, kriegi, leopardinus, monlicola, nigromaculatus, nigroviridis, pielus and tenuis. Interestingly, most of the groups indicated above are endemic to areas that have recently been described as areas of high endemism for southern South America.